Digital Business Opportunities in the 5.0 Era: Preparing Dayah Darul Hikmah Students Who Are Ready to be Entrepreneurs - Elianti Nasution, Lisa; Rezeki, Sri; Setyorini, Dian; Hamat, Zahri; Haris Riyaldi, Muhammad; Sari, Nurma; Hidayat, Firdan; Martin Sitepu, Panglima (Eastasouth Journal of Positive Community Services, 2025)
The transformation towards the Society 5.0 era requires the younger generation to have adaptive skills to digital technology, including in the field of entrepreneurship. However, students in religious education institutions such as dayah still face limited access to information and training related to digital business opportunities. This community service activity was held at Dayah Darul Hikmah, Baitussalam District, Aceh Besar, on Friday, February 14, 2025, and was attended by 50 students. The purpose of this activity is to increase digital literacy and foster the spirit of entrepreneurship among students through interactive training. The implementation method includes interactive lectures, group discussions, and simple digital business practice workshops. The results of the activity showed that participants experienced an increased understanding of digital business concepts and were able to develop business ideas that were contextual with the surrounding environment. The positive response from the participants and the dayah showed that this activity succeeded in raising awareness of the importance of digital literacy and entrepreneurship. The follow-up plan includes an ongoing mentoring program, the preparation of learning modules, collaboration with strategic partners, and periodic evaluations of participants' development.